Cognitive fog for health: a distributed solution for smart city. (4th May 2020) - Chen, Shu; Chen, Nanxi; Tang, Jiayi; Wang, Xu
The internet of things (IoT) connects numerous physical devices in urban areas to implement smart cities, and health monitoring has emerged as the most promising application area in such cities. However, the current health monitoring solution heavily relies on cloud-based data centres to integrate data, which put the city's confidential data and user's private information at risk of leakage. Fog computing as an extension of cloud computing has attracted lots of attention in the IoT community, for its safety to local data and friendliness to time-sensitive applications. This article adopts the paradigm of fog computing and proposes the cognitive fog for health (CFH) to address the requirement of estimating urban-level health impact in the real-world scenario.